CLINICAL COURSE AND PROGNOSIS OF «NEAR MISS» ECTOPIC PREGNANCY - LARISA E. Fetischeva; VADIM G. Mozes; IGOR S. Zakharov; T. M. Sokolova (Фундаментальная и клиническая медицина, 2018)
Aim. To identify risk factors for «near miss» ectopic pregnancy. Materials and Methods. We recruited 720 consecutive women with ectopic pregnancy who were admitted to the gynecology unit of a large multidisciplinary hospital from 2007 to 2017. All patients were divided into two groups: without «near miss» (n = 666) and with «near miss» ectopic pregnancy (n = 54) defined by potentially life-threatening conditions such as massive (> 1500 mL) intraabdominal bleeding, multiple organ failure syndrome, or sepsis. Short-term outcomes were evaluated on the 6th day postoperation. Results. Certain risk factors for «near miss» were uncontrollable such as cardiovascular disease (OR = 3.2, 95% CI = 1.0-9.8, p = 0.004) and past medical history of obstetric or gynecological disorders, in particular spontaneous miscarriage (OR = 15.6, 95% CI = 7.7-31.7, p = 0.001). Controllable risk factors included rare types of ectopic pregnancy (OR = 3757.4, 95% CI = 625-30567, p = 0.001) such as interstitial pregnancy (OR= 896.3, 95% CI = 121.3-1864.4, p = 0.001). Conclusion. Rare types of ectopic pregnancy represent a valuable predictor of «near miss» condition.